2020
DOI: 10.1186/s12888-020-02571-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among carers and the moderating effects of social support

Abstract: Background: Carers provide both practical and emotional support and often play an important role in coordination of care for recipients. The demands of caring may lead to increased levels of stress for the carer, which can affect mental health and quality of life. This study examined the relationship between being a carer and psychological distress (assessed using the Kessler Psychological Distress Scale [K10]), and explored the moderating effect of social support in that relationship using a large sample. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 30 publications
5
46
2
1
Order By: Relevance
“…Our study further showed that caregivers of patients with ED got less social support. A recent study showed that treatments addressing social support are beneficial in reducing the psychological burden on caregivers (George, Kecmanovic, Meade, & Kolt, 2020). But the relationship between social support and negative feelings needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further showed that caregivers of patients with ED got less social support. A recent study showed that treatments addressing social support are beneficial in reducing the psychological burden on caregivers (George, Kecmanovic, Meade, & Kolt, 2020). But the relationship between social support and negative feelings needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that more than one in three family caregivers felt that they could not continue their role and had reached 'breaking point' [8]. Caregiving has also been linked with negative impacts on quality of life [9,10]. As carers are often overwhelmed by the demands of caring for their relatives with SMI, they are frequently under considerable stress [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment strategies should consider both the patients and caregivers/relatives as a single unit: patients are assessed and treated for disorders, and caregivers/relatives are assessed on their well-being and ability to provide care. Clinicians could then suggest resources for strategies (e.g., Goal Attainment Scaling (Chew et al, 2015) ), self-care (Furlong & Wuest, 2008;Lu & Wykle, 2007;McCabe et al, 2016) , and social support (George et al, 2020) for caregivers/relatives.…”
Section: Discussionmentioning
confidence: 99%